Analisis Pengaruh Green Marketing, Citra Merek dan Kualitas Layanan Terhadap Minat Pembelian Ulang Makanan Halal Cepat Saji di Mcdonald’s - Anggreani, Niken; Mardalis, Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of green marketing, brand image, and service quality on the repurchase intention of fast food halal products at McDonald’s. This research was conducted using quantitative methods with data collection techniques using questionnaires. The sampling technique used purposive sampling technique. Validity and reliability tests using smart PLS analysis on the outer model. Hypothesis testing using the smartPLS inner model. The results show that green marketing has a positive and significant effect on repurchase intention, as indicated by a t-statistic value of 3.162 and a p-value of 0.002. Brand image also has a positive and significant effect on repurchase intention, with a t-statistic value of 5.026 and a p-value of 0.000. Additionally, service quality has a positive and significant effect on repurchase intention, with a t-statistic value of 6.865 and a p-value of 0.000. These findings suggest that improvements in green marketing, brand image, and service quality can increase consumers' repurchase intention for fast food halal products at McDonald’s. The practical implications of this research indicate that McDonald’s should focus on environmentally friendly marketing strategies, maintain a strong brand image, and enhance service quality to build customer loyalty and boost sales.